2011
DOI: 10.1186/1897-4287-9-8
|View full text |Cite
|
Sign up to set email alerts
|

Lynch syndrome: barriers to and facilitators of screening and disease management

Abstract: BackgroundLynch syndrome is a hereditary cancer with confirmed carriers at high risk for colorectal (CRC) and extracolonic cancers. The purpose of the current study was to develop a greater understanding of the factors influencing decisions about disease management post-genetic testing.MethodsThe study used a grounded theory approach to data collection and analysis as part of a multiphase project examining the psychosocial and behavioral impact of predictive DNA testing for Lynch syndrome. Individual and small… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
51
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(56 citation statements)
references
References 50 publications
5
51
0
Order By: Relevance
“…[24][25][26] Some families affected by Lynch syndrome in our jurisdiction have also suggested that prohibitive costs are a barrier to recommended colon cancer screening and ongoing risk management. 29 Beyond these direct costs, however, study findings revealed the breadth of perceived economic impact associated with ARVC, consistent with a recent systematic review that suggested that indirect costs were as burdensome for sufferers of rare diseases as direct costs. 25 Even unaffected participants can perceive significant economic burden.…”
Section: Discussionsupporting
confidence: 84%
“…[24][25][26] Some families affected by Lynch syndrome in our jurisdiction have also suggested that prohibitive costs are a barrier to recommended colon cancer screening and ongoing risk management. 29 Beyond these direct costs, however, study findings revealed the breadth of perceived economic impact associated with ARVC, consistent with a recent systematic review that suggested that indirect costs were as burdensome for sufferers of rare diseases as direct costs. 25 Even unaffected participants can perceive significant economic burden.…”
Section: Discussionsupporting
confidence: 84%
“…Compared with the general population, MMR mutation carriers have a higher lifetime risk for several cancers; CRC risk ranges from 20 to 69% for men and 10 to 52% for women, with risks varying based on mutated gene [9][10][11][12][13]. Women with LS also have a 40-60% lifetime risk for developing endometrial cancer [2,3,8,14]. Individuals with LS are at increased risk for other malignancies, including ovarian, stomach, small bowel, hepatobiliary tract, pancreatic, urinary tract, brain, and skin cancers [3,8,14].…”
Section: What Is Ls?mentioning
confidence: 99%
“…Study participants expressed higher levels of trust when physicians were both aware of their family history and recognized the importance of high‐risk cancer surveillance . These factors also influenced participation in recommended screening regimens . However, further research is needed to fully examine how patient trust can be effectively improved .…”
Section: Introductionmentioning
confidence: 99%
“…A history of psychosocial problems or depression has been found to correlate with increased anxiety and distress after genetic testing [12-14]. Also, coping style, external and internal factors such as personal resources, risk perception, social networks, interaction with health care providers and access to psychosocial support have been found to influence the ability to handle knowledge about an increased risk of cancer [15,16]. Though few studies have evaluated the long-term consequences of living with a high risk of cancer, a number of issues have been identified as challenging, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Individuals with a positive self-concept are more apt at enduring stressful situations as opposed to those with a more negative perception of the self [21]. Self-concept scales for different types of hereditary cancer have been developed [16,22-24]. The Lynch syndrome self-concept scale contains two subscales related to stigma and vulnerability and to gastrointestinal-related anxiety.…”
Section: Introductionmentioning
confidence: 99%